INNOVATIVE ACTUATION MECHANISM FOR ENHANCED EFFICIENCY IN DEVELOPING PLACER MINERAL DEPOSITS AND PEAT USING BULLDOZER BLADE WITH DETACHABLE CUTTING - Yevgeniy Chsherbinin; Amandyk Tuleshov; Maksat Kalimoldayev; Talgat Kaiym; Askar Seidakhmet; Orken Mamyrbayev; Suleimen Kaimov; Aidarkhan Kaimov (Theoretical Hypotheses and Empirical Results, 2023)
This article centers around the quest to amplify the efficiency of developing placer mineral deposits and peat through the integration of earth-moving and construction machinery. The core of this study introduces a pioneering actuation mechanism tailored for the operational segment of a bulldozer blade. This groundbreaking mechanism showcases a distinctive detachable cutting knife. The research venture encompasses the creation of a comprehensive mathematical model that not only aids in determining the mechanism’s geometric, structural-kinematic, and dynamic attributes but also takes into account the stochastic processes inherent in its interaction with the surrounding operational environment. A crucial aspect of this study lies in addressing the imperative to accommodate the dual factors of variability originating from random parameter errors, which may diverge from the "ideal" design models, and systematic errors intricately tied to measurement precision. This intricate balance is achieved by integrating a recurring procedure for pinpointing the optimal weighting factor, utilizing the Kalman methodology. The strategic determination of the structural, kinematic, and dynamic parameters for the inventive blade featuring the detachable cutting knife rests on the fundamental principle of adapting to the resistance force exerted by the terrain, thereby establishing the optimal layer thickness. The genesis of the revolutionary bulldozer, which incorporates the detachable cutting knife, is firmly rooted in mathematical methodologies, forming the bedrock for its actualization. Consequently, this inventive bulldozer design has achieved the notable milestone of securing a patent from the Republic of Kazakhstan.